THE IMPACT OF MODERN MARKETS TOWARD INCOME OF TRADITIONAL MARKET TRADERS - Sugiono Sugiono; Tukasno Tukasno; Taufiq Taufiq (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The Way Jepara traditional market is a market whose management is still carried out conventionally and the interaction between traders and buyers is very intense. There is a bargaining process between traders and buyers to reach a price agreement that is considered appropriate for both parties. This condition is in stark contrast to the modern market which is starting to grow and develop rapidly in Way Jepara whose management concept is already organized and systemized. In modern markets, the interaction between traders and buyers is minimal because they have implemented the concept of self-service, which means that buyers serve themselves. This study aims to determine the difference in the income of Way Jepara market traders before and after the existence of the modern market. This research method uses a comparative research type to determine the difference in the income of Way Jepara market traders before and after the existence of the modern market. The data analysis used is the Related Sample t-Test because the income data used in this study is ratio data. The results of this study indicate that there is a significant difference in the income of Way Jepara traditional market traders between before and after the existence of the modern market. Thus the research hypothesis is accepted. Keywords: Income, Traditional Markets, Modern Markets, Traders, Economics